MENGAWAL IMPLEMENTASI PEMBUKUAN BERJENJANG BUMDES MASKUMAMBANG - Yokhebed Widhianingtyas; Adinda Elsinta Damayanti; Marcelina Novenda Gissela Anggari; Christian Alessandro Noreen; Theresia Woro Damayanti; Ari Budi Kristanto; Supatmi Supatmi; Ocsa Nugraha Saian (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
BUMDes is expected to be a source of economic development for rural communities. This expectation must be able to be answered by BUMDes through the preparation of accountable and organized bookkeeping. This community service is carried out at the BUMDes Maskumambang which is not yet fully capable of preparing accounting bookkeeping. The purpose of community service at BUMDes Maskumambang is as a form of academic participation to the community to help overcome the problems that occur. The implementation of community service at BUMDes Maskumambang intends to increase understanding of the importance of the bookkeeping system at BUMDes Maskumambang. The community service is carried out by assisting in the preparation of financial report templates, counseling and training on financial report templates for BUMDes employees. The result of this community service is an increase in the understanding of BUMDes employees on the importance of accountable and organized bookkeeping also identification of the needs of BUMDes Maskumambang.